Chaotic motion of dynamic systems with “one” degree of freedom - Buts, V.A. (Вопросы атомной науки и техники, 2012)
It is shown that the regimes with chaotic motion are also inherent in dynamic systems having only one degree of freedom. Such opportunity arises because such systems in the phase space have areas in which the conditions of the uniqueness theorem are broken, in particular, in the presence of singular solutions. Examples of such systems are given. Показано, что режимы с хаотическим движением присущи также динамическим системам, имеющим всего одну степень свободы. Такая возможность возникает благодаря тому, что такие системы в своем фазовом пространстве имеют области, в которых нарушаются условия теоремы единственности, в частности, при наличии особых решений. Приведены примеры таких систем. Показано, що режими з хаотичним рухом властиві також динамічним системам, що мають усього один ступінь свободи. Така можливість виникає завдяки тому, що такі системи у своєму фазовому просторі мають області, у яких порушуються умови теореми єдності, зокрема, при наявності особливих рішень. Наведено приклади таких систем.